Tour Sci Soc Kor 2016
DOI: 10.17086/jts.2016.40.8.193.203
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relationships among Mobile Augmented Reality Technology at a Tourist Spot, Experiential Value and the Subsequent Positive Recall of Historical Culture Sites

Abstract: This case study analyzed mobile augmented reality technology at a tourist spot and the subsequent positive recall of historical culture sites. It particularly tested the mediating effects of experiential value on the relationships between mobile augmented reality technology at a tourist spot and subsequent positive recall. By doing so, this study provides implications that suggest the need to examine the mobile augmented reality technology’ presence and to find out its effects on tourism experience throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The second study by Kang (2016) analyzed the use of mobile AR technology at a tourist spot and its positive recall of historical cultural sites. The study found that mobile AR technology positively influences experiential value and positive recall.…”
Section: Empirical Research On Ar For History Educationmentioning
confidence: 99%
“…The second study by Kang (2016) analyzed the use of mobile AR technology at a tourist spot and its positive recall of historical cultural sites. The study found that mobile AR technology positively influences experiential value and positive recall.…”
Section: Empirical Research On Ar For History Educationmentioning
confidence: 99%